The role of yoghurt on dental erosion - Zayadi, Alisa; Bikarindrasari, Rini; Anastasia, Danica (Padjadjaran Journal of Dentistry, 2014)
Dental erosion is defined as irreversible loss of dental hard tissue, caused by acid condition in the oral cavity without bacterial involvement. One of the signs of dental erosion is calcium dissolution of the enamel. Yoghurt is a fermented beverage that has low pH level due to lactic acid. The aim of this study was to measure the solubility of calcium enamel after soaking in yoghurt for 12 and 18 hours. Twenty-four premolars were divided into 4 groups. Group A and B were soaked in milk for 12 and 18 hours; group C and D were soaked in yoghurt for 12 and 18 hours. Atomic Absorption Spectrophotometer (AAS) was used to measure the solubility of calcium from each sample. Data were analyzed using one-way ANOVA and LSD (p < 0.05). This study indicated that soaking premolars in yoghurt for 18 hours has greater enamel calcium dissolution than in yoghurt for 12 hours. It can be concluded that prolonged soaking premolars in yoghurt will increase the calcium enamel dissolution.